Unlocking the Potential for Private Sector Participation in District Heating - International Finance Corporation (Washington, DC, 2015)
The report analyzes barriers to and opportunities for private sector participation in district heating (DH) in the Western Balkan countries of Bosnia and Herzegovina, Croatia, Kosovo, and Serbia, as well as in Mongolia and Ukraine. Specifically, the report analyzes the legal and regulatory frameworks for public-private partnerships (PPP) and for DH in each of the countries,including an overview of the primary and secondary legislation, PPP preparation and approval processes, institutional setup of the DH sector, heat tariff-setting procedures, etc. In addition, the report describes international best practice for various business models for private sector participation in DH and provides country-specific recommendations to improve the attractiveness of PPP in the DH sector. Finally, the report provides an estimation of the investment needs in the DH sector by country and indicates selected investment projects, which are conservatively assessed at 1.5 billion dollars.